Cork-oak woodlands as key-habitats for biodiversity conservation in Mediterranean landscapes: a case study using rove and ground beetles (Coleoptera: Staphylinidae, Carabidae) - Silva, Pedro Martins; Aguiar, Carlos a S.; Niemelä, Jari; Sousa, José Paulo; Serrano, Artur R. M.; da Silva, Pedro Martins; Aguiar, Carlos a S.; Niemelä, Jari; Sousa, José Paulo; Serrano, Artur R. M. (Biodiversity and Conservation, 2008)
Land-use intensiﬁcation in Mediterranean agro-forest systems became a pressure on biodiversity, concerning particularly the woodland sensitive species. In 2001, the effects of a land-use gradient from old-growth cork-oak forest to a homogeneous agricultural area were assessed using rove beetles as indicators in a Mediterranean landscape. The aim was to ﬁnd which species were negatively affected by land-use intensiﬁcation at the landscape level and whether they beneﬁted from cork-oak patches occurring along the land-use gradient. A total of 3,196 rove beetles from 88 taxa were sampled from all landscape types. Agricultural area recorded signiﬁcantly higher numbers of abundance and species richness in relation to the cork-oak mosaics, i.e. the old-growth forest and the managed agro-forest landscapes (montados). Moreover, 70% of rove beetle indicator species common enough to be tested by IndVal displayed their highest indicator value for agriculture, showing a lower number of woodland indicators in comparison to ground beetles. Nevertheless, one rove beetle taxon was considered a specialist of closed woodland mosaics while no specialist ground beetle was found for that landscape typology. Some rare rove beetle species were also important in typifying diversity patterns of oldgrowth cork-oak forests. Hence, future management in Mediterranean landscapes should take into account not only indicator species common enough to be tested by IndVal, but also rare and endemic species. Considering the added value of cork-oak woodland cover for sensitive rove and ground beetle diversity, the strengthening of cork-oak woodland connectivity seems to be a crucial management that is required in agricultural Mediterranean landscapes.
Keywords: á; agro-forest mosaic; agro-forest mosaic á biodiversity; Biodiversity conservation; conservation á epigaeic coleoptera; epigaeic coleoptera; indicator value; indicator value á land-use; intensification á quercus suber; land-use intensification; Quercus suber

Cork-oak woodlands as key-habitats for biodiversity conservation in Mediterranean landscapes: a case study using rove and ground beetles (Coleoptera: Staphylinidae, Carabidae) - Silva, Pedro Martins; Aguiar, Carlos a. S.; Niemelä, Jari; Sousa, José Paulo; Serrano, Artur R. M.; da Silva, Pedro Martins; Aguiar, Carlos a. S.; Niemelä, Jari; Sousa, José Paulo; Serrano, Artur R. M. (Biodiversity and Conservation, 2008)
Land-use intensiﬁcation in Mediterranean agro-forest systems became a pressure on biodiversity, concerning particularly the woodland sensitive species. In 2001, the effects of a land-use gradient from old-growth cork-oak forest to a homogeneous agricultural area were assessed using rove beetles as indicators in a Mediterranean landscape. The aim was to ﬁnd which species were negatively affected by land-use intensiﬁcation at the landscape level and whether they beneﬁted from cork-oak patches occurring along the land-use gradient. A total of 3,196 rove beetles from 88 taxa were sampled from all landscape types. Agricultural area recorded signiﬁcantly higher numbers of abundance and species richness in relation to the cork-oak mosaics, i.e. the old-growth forest and the managed agro-forest landscapes (montados). Moreover, 70% of rove beetle indicator species common enough to be tested by IndVal displayed their highest indicator value for agriculture, showing a lower number of woodland indicators in comparison to ground beetles. Nevertheless, one rove beetle taxon was considered a specialist of closed woodland mosaics while no specialist ground beetle was found for that landscape typology. Some rare rove beetle species were also important in typifying diversity patterns of oldgrowth cork-oak forests. Hence, future management in Mediterranean landscapes should take into account not only indicator species common enough to be tested by IndVal, but also rare and endemic species. Considering the added value of cork-oak woodland cover for sensitive rove and ground beetle diversity, the strengthening of cork-oak woodland connectivity seems to be a crucial management that is required in agricultural Mediterranean landscapes.
Keywords: á; agro-forest mosaic; agro-forest mosaic á biodiversity; Biodiversity conservation; conservation á epigaeic coleoptera; epigaeic coleoptera; indicator value; indicator value á land-use; intensification á quercus suber; land-use intensification; Quercus suber

Use of direct gradient analysis to study the climate-vegetation relationships in Galicia, Spain - Retuerto, Ruben; Carballeira, Alejo (Plant Ecology, 1992)
This paper reports a bioclimatic analysis of plant species in Galicia, NW Spain. A set of floristic data obtained from 150 plots located at euclimatopes (sites with monitored climate) was analysed using di- rect gradient analysis and clustering with respect to the 8 climatic variables thought to play a major role in regulating the distribution of the species considered in the study area. Principal component analysis (PCA) and hierarchical clustering were based on a matrix of species by climatic variables. Indicator taxa for the variables were identified on the basis of their Indicator values (Brisse & Grandjouan 1978) and grouped by cluster analysis. The groups produced were compatible with the results of principal com- ponent analyis and the frequential analysis of the species, which identified their phytoclimatic nature. The groups were then characterized by determining their climatic positions and indicator values with respect to the chief climatic variables. The first three PCA axes, which were associated with Oceanity, Mean minimum temperatures and the temperature range in the coldest month, together accounted for 97.2 ~o of the variance of the data.
Keywords: climatic factors; climatic position; Clustering; frequential analysis; indicator value; phytoclimatology; Principal component analysis